Surface free energy and geometric structures of the surfaces of selected epoxy composites - Rudawska, A. (Polimery, 2022)
Polymeric composites have been characterized as constructional materials. The significance of surface free energy and geometric structure of the surface was emphasized. Three types of epoxy composites differing in reinforcing fillers (glass, aramid or graphite ones) (Table 1) were subjects of investigations. Surface free energy (?s) of the composite and its polar and dispersive components (?sp and ?sd, respectively) were characterized by Owens-Wendt method (Fig. 1-3). Geometric structures of the samples' surfaces were evaluated with use of scanning electron microscope (SEM) (Fig. 4- 6). The values of vs are rather high independently on the reinforcing component used (44-46mJ/m2) what means good adhesive properties. Clear differences in geometric structures of the samples' surfaces (e.g. the degrees of waviness or roughness) do not reflect ?s values.